Perlindungan Hukum Terhadap Anak di Bawah Umur Korban Prostitusi Online Melalui Aplikasi Michat di Kota Kendari - Ni Putu Sri Widiasih; Isnayanti; Idris Saputra; Dewi Ratnasari Rustam; Asyifa Putri Siva (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This research is entitled "Legal Protection for Minors Victims of Online Prostitution Through the Michat Application in Kendari City." The actual situation that is intended to be realized through the Child Protection Law is the protection and guarantee of children's rights from all actions or deeds that are detrimental to them. Children, as the next generation of the nation's ideals in their growth and development, have the right to protection from sexual violence, torture, and treatment that degrades their dignity as human beings. Children must receive protection so that they do not become victims of any crime, including sexual violence committed directly or indirectly by individuals, groups, or the government. The very rapid development of information technology has both positive and negative impacts on people's lives. One of the most disturbing negative impacts is the increase in sexual crimes against children in cyberspace. Children as a vulnerable group require special legal protection due to their inability to defend themselves physically and mentally. This study aims to determine how the regulation and implementation of legal protection for children as victims of prostitution through the Michat application in Kendari City. This research is interesting for examining the legal protection model, as legal protection is key to realizing the ideals of law itself: legal certainty, justice, and utility. This article employs a normative, empirical legal research approach, drawing on primary and secondary legal sources, utilizing three approaches to the problem: the statute approach, the conceptual approach, and the case approach.